Coenological investigations of snails (Mollusca: Gastropoda) in some phytocoenoses of the Bijele Stijene (Velika Kapela, Croatia, Yugoslavia) - Toni Nikolić; Vesna Štamol (Acta Biologica Slovenica)
The present paper presents the results of the coenological investigations of snails performed in 5 phytocoenoses of the Bijele Stijene. The relative abundance, the number of the snail taxa, density of a single taxon and the density of the coenoses have been established. The snail communities were compared according to the S0RENSEN similarity quotient and grouped according to the UPGMA technique. A total of 38 snail taxa have been established. Only partial overlapping between the snail communities and the corresponding plant unions was observed.